360 Degree Performance Appraisals of Students: a Demographic Study - Jain, A; Hyde, A. M; Sharma, B (International Journal of Computer Sciences and Engineering, 2025)
Performance appraisal is one of the functions of Human Resource Management for measuring and evaluating the performance of the employees in an organization over a period of time as against the set standards. Performance appraisal (PA) which is a process used by the firms to evaluate their employees’ efficiency and productivity, was initially carried out by the supervisors. 360 Degree Performance Appraisal is also identified as, is feedback which comes from different groups of reviewer who socialize with evaluated employees. For the most part this feedback will incorporate assessment from subordinates, colleagues, and his superior and in addition without anyone else specifically. It can likewise incorporate, now and again, feedback from external sources, for example, customers and suppliers or other intrigued stakeholders. 360 degree criticism ought to be utilized solely for advancement purposes, or ought to be utilized for examination purposes too. 360 degree feedback is utilized for two purposes i.e. assessment and development. In this Research Primary data has been collected from students of various streams of Indore Division through using a Self Designed Questionnaire. T-Test and One way ANOVA test have been applied for the purpose of study A Demographic Study on Factors Determining 360 Degree Performance Appraisals of Students. Normality and Reliability have been checked. The purpose is to find out the contribution of 360 degree feedback to the students. Various benefits and shortcoming are listed down while introducing this method in the organization